E-THERAPY UNTUK MENINGKATKAN EFIKASI AKADEMIK DAN MENURUNKAN STRES PADA REMAJA DENGAN KONFLIK ORANGTUA-ANAK - , ASWENDO DWITANTYANOV, Dr. Neila Ramdhani, M.Si., M.Ed. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Every student needs to have self-efficacy of their own abilities to cope with burdens and academic demands. Relationship problem between parent-children can be the stressor that will affect self-efficacy and academic achievement. The aim of this research is to find out the role of internet support group therapy based on humanistic approach method for improving self-effication and reducing stress level on adolescent who have parent-children conflict. The participants of this research are five adolescents who have parent-children conflict. This research will use single-case subject method with B-A-B desing. All datas will be collected by self-efficacyâs scale (Î±= 0,862, DASS-21 (Î±= 0,720), Ana checklist as additional tools to control individualâs complaint between sessions of the intervention. For getting more richer result from qualitative data, this research will be equipped with interview and observation technique. Hypothesis was tested by using visual inspection and qualitative analysis based on documents during the process of therapy and follow-up interview. The results showed a change in the dependent. Stress levels in each participant has decreased and academic self-efficacy in each participant experiencing an increase.